If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + iy = 1 Reorder the terms: iy + x = 1 Solving iy + x = 1 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-1x' to each side of the equation. iy + x + -1x = 1 + -1x Combine like terms: x + -1x = 0 iy + 0 = 1 + -1x iy = 1 + -1x Divide each side by 'y'. i = y-1 + -1xy-1 Simplifying i = y-1 + -1xy-1 Reorder the terms: i = -1xy-1 + y-1
| (8-2x)(12-2x)x=0 | | 3(s+1)+1=19 | | 9c-8=-5 | | -2-17g=-18g-20 | | 8(n-7)-2(4n+5)=5n-3+5n+7 | | (X-5)/62 | | 2+17d=11d-16 | | 4x-15=2x-17 | | (X-5)/6/ | | x^2-9=91 | | .10d+.25q=3.60 | | 6b+6=12 | | 4x-15=3x-17 | | 37=16t^2+484 | | -15.5r+19.61=8.3r-12.24+0.7 | | (4*x)-7=58-x | | x^2-12+36=12 | | 29x+3=28x+7 | | 5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5+5=50 | | 2/3x2.6= | | 3-6v=45 | | 6-5/6= | | -4+s=68 | | 18+7x=-3(5-5x)-7 | | (-5x^3y)*(-10x^4y^2)=0 | | y=20x^2-105x-90 | | 0.09xX=102.84 | | x+(-13.4)=(-1.7) | | 4x+2x+5x=55 | | 4d-3=6 | | 7x+x-117=35 | | 6(x+38)=258 |